Innovative Assessment Instruments for KESAN Ethnoscience Learning Model - Irfan Ananda Ismail; Festiyed; Sulistya Yuda; Amir Karimi; Yumi Ariyati (Journal of Global Research Education, 2025)
The evolution of inquiry-based learning has reached a critical juncture where traditional Western-centric approaches prove insufficient for culturally diverse educational contexts, creating an urgent need for innovative assessment methodologies. This study addresses a fundamental gap in educational research: the absence of specialized instruments capable of evaluating pedagogical innovations that transcend conventional inquiry learning limitations through systematic cultural knowledge integration. We present the development of a comprehensive assessment framework specifically designed for the KESAN (Konektivitas Etnosains-Sains) learning model, representing a revolutionary advancement from classical inquiry through guided inquiry to synthetic epistemological integration. Using Educational Design Research (EDR) methodology, we systematically developed five specialized instruments that collectively address critical evaluation gaps: (1) Content Assessment Instrument for evaluating dual-epistemological curriculum integration; (2) Construct Validation Instrument for assessing theoretical coherence in synthetic investigation approaches; (3) Teacher Practicality Instrument for measuring implementation feasibility of culturally-sustaining pedagogy; (4) Student Practicality Instrument for evaluating identity-affirming learning experiences; and (5) Communication and Implementation Framework for systematic deployment and research dissemination. This research represents the first systematic attempt to create assessment tools specifically designed for evaluating educational innovations that achieve authentic cultural knowledge integration without compromising scientific rigor